The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1021/acs.jpcb.1c01245
|View full text |Cite
|
Sign up to set email alerts
|

On the Segmental Dynamics and the Glass Transition Behavior of Poly(2-vinylpyridine) in One- and Two-Dimensional Nanometric Confinement

Abstract: Geometric nanoconfinement, in one and two dimensions, has a fundamental influence on the segmental dynamics of polymer glass-formers and can be markedly different from that observed in the bulk state. In this work, with the use of dielectric spectroscopy, we have investigated the glass transition behavior of poly(2-vinylpyridine) (P2VP) confined within alumina nanopores and prepared as a thin film supported on a silicon substrate. P2VP is known to exhibit strong, attractive interactions with confining surfaces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 114 publications
(237 reference statements)
1
5
0
Order By: Relevance
“…Separately, there are tendencies for the chain ends, which possess more free volume than chain segments do, to segregate to the free surface and for the density of chain entanglement near the surface to be smaller than that in the bulk. , All of these factors can lead to enhancements in the near-surface mobility ,, and reductions in the T g of thin polymer films ( T g film ). ,,, On the other hand, the surface chemistry ,, and stiffness of the substrate supporting the films, and the near-substrate chain conformations , can affect the dynamics of the nearby polymer. Combinations of the free surface and substrate effects can produce a variety of thickness dependences of the thin film dynamics as found in experiments. ,,,, …”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Separately, there are tendencies for the chain ends, which possess more free volume than chain segments do, to segregate to the free surface and for the density of chain entanglement near the surface to be smaller than that in the bulk. , All of these factors can lead to enhancements in the near-surface mobility ,, and reductions in the T g of thin polymer films ( T g film ). ,,, On the other hand, the surface chemistry ,, and stiffness of the substrate supporting the films, and the near-substrate chain conformations , can affect the dynamics of the nearby polymer. Combinations of the free surface and substrate effects can produce a variety of thickness dependences of the thin film dynamics as found in experiments. ,,,, …”
Section: Introductionmentioning
confidence: 89%
“…Many studies involving polymer films with thicknesses ( h ) below ca. 100–1000 nm have revealed the so-called confinement effect, namely, variations in the physical properties of the films with h , including the glass-transition temperature ( T g ), viscosity, and elastic modulus. The thickness dependences of these properties have generally been attributed to perturbations by the free (or air) surface and substrate interface to the mobility of the near-surface segments. ,, At the free surface, the density of the polymer decreases rapidly to zero within a small distance of ∼1 nm . Furthermore, the average number of nearest neighbors per segment in this region is reduced by a large fraction from that in the bulk.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The glass transition temperature, T g , is a key characteristic of polymer materials because many physical and mechanical properties change markedly when a polymer undergoes a glass transition from a rubbery state to a glassy state or vice versa. , For polymer films confined at the nanoscale, perturbations originating at the polymer/free surface and the polymer/solid interfaces often result in deviations of the measured T g from the bulk T g . Such nanoconfinement behavior is important because it can affect the commercial application of ultrathin polymer films and may aid in understanding the underlying mechanisms of glass transition behavior, which has been a long-standing, unresolved challenge. Indeed, the T g -confinement behavior of polymers has been the subject of intense research since 1994 when Keddie et al , first reported that, relative to bulk T g , the T g s of polystyrene (PS) and poly­(methyl methacrylate) ultrathin films supported on silicon decrease and increase, respectively, with decreasing nanoscale thickness.…”
Section: Introductionmentioning
confidence: 99%
“…However, when the materials are confined by their thickness, they show a lot of anomalous behavior compared to their bulk counterparts. This can include various properties such as its density, dynamics, crystallization, stability, , and so forth. This is where the challenges in the practical implementation of a confined system lie.…”
Section: Introductionmentioning
confidence: 99%